Clinical features of 123 patients with hyperinsulinemic hypoglycemia auxiliarily diagnosed by 18F-DOPA-PET CT scanning - Zhang, M Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To summarize the clinical features and therapeutic outcomes of patients with hyperinsulinemic hypoglycemia (HH) auxiliarily diagnosed by 18F-DOPA positron emission tomography (PET) CT scanning. Methods: The clinical data of 123 patients who were diagnosed with hyperinsulinemic hypoglycemia by comprehensive clinical diagnostic procedures in the Department of Pediatric Endocrinology and Inherited Metabolic Diseases, Children's Hospital of Fudan University between January 2016 and December 2020 were retrospectively analyzed. Clinical data such as gender, age of onset, province, concurrent serum insulin level measured during hypoglycemia, lesion type of pancreas by 18F-DOPA-PET CT scanning, genetic test results, and treatment were collected successively. The clinical features and therapeutic outcomes were compared between patients with focal and diffuse pancreatic lesions. T test, Rank sum test, and χ² test were used for comparison between groups. Results: A total of 123 patients with hyperinsulinemic hypoglycemia (72 males and 51 females), whose average age of onset was 3 days (ranging from 1 day to 4 860 days), were recruited from 24 provinces. The concurrent serum insulin level was 7.1 (0.4-303.0) mU/L during hypoglycemia. 18F-DOPA-PET CT scanning identified focal lesions in 25.2% (31/123) and diffuse lesions in 74.8% (92/123) of the patients; 64.2% (79/123) of the HH cases were found to have pathogenic gene variants, in which 88.6% (70/79) were found to have KATP channel related genes (61 in ABCC8 and 9 in KCNJ11 mutations). Thirty-seven patients (17 focal and 20 diffuse) received surgical treatment with a success rate of 67.6% (25/37). The effective rate of diazoxide for children with diffuse type was significantly higher than that of children with focal group (28.3% (26/92) vs. 9.7% (3/31), χ²=10.31, P=0.001). Conclusions: 18F-DOPA-PET CT scan can improve the success rate of surgery. Comprehensive diagnosis of the etiology of hyperinsulinemic hypoglycemia by genetic analysis and 18F-DOPA-PET CT scanning can result in better treatment and prognosis